Alanna ebook The first adventure. - Pierce, Tamora (Song of the Lioness, 2006)
A girl disguises herself as a boy to train as a knight in this first book in Tamora Pierce's Margaret A. Edwards Award–winning young adult series—now with a new look! From now on, I'm Alan of Trebond, the younger twin. I'll be a knight. In a time when girls are forbidden to be warriors, Alanna of Trebond wants nothing more than to be a knight of the realm of Tortall. So she finds a way to switch places with her twin brother, Thom, and, disguised as a boy, begins her training as a page at the palace of King Roald. But the road to knighthood, as she discovers, is not an easy one. Alanna must master weapons, combat, and magic, as well as polite behavior, her temper, and even her own heart. So begin Alanna's adventures—filled with swords and sorcery, adventure and intrigue, good and evil—that will lead to the fulfillment of her dreams and make her a legend in the land.